TRANSPARANSI DAN AKUNTABILITAS SEBAGAI INDIKATOR GOOD GOVERNANCE: STUDI PADA DESA KENTENG - Iva Sofi Gunawati; Nurdian Susilowati; Amir Mahmud (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2026)
This study aims to analyze the transparency and accountability of Village Fund (Dana Desa) management in Kenteng Village, Bandungan District, Semarang Regency. The research focuses on the stages of planning, implementation, administration, as well as financial reporting and accountability. Using a descriptive qualitative approach, data were collected through in-depth interviews with village officials, field observations, and a review of official documents such as the Village Budget (APBDes) and budget realization reports. The findings indicate that the management of Village Funds in Kenteng Village has been carried out in a participatory manner through hamlet-level and village-level deliberations, involving the Village Consultative Body (BPD), community leaders, youth representatives, and women’s groups. Program implementation refers to formal documents such as the RKPDes, APBDes, DPA, and DPPA, and is conducted transparently through the installation of information boards at project locations. Financial administration utilizes the Siskeudes application, ensuring orderly, accurate, and accountable recording. Financial reporting is conducted semi-annually in accordance with regulations, although occasional delays occur due to technical constraints and incomplete documentation from activity implementers. Overall, Village Fund management in Kenteng demonstrates strong elements of transparency and accountability, yet still requires improvements in human resource capacity and optimization of information technology. This study provides empirical insight into village financial governance and is expected to serve as input for village governments and stakeholders in strengthening effective, efficient, and participatory Village Fund management